Two new species of Russula subgenus Heterophyllidia (Russulaceae, Russulales) from Yanshan Mountains, North China - Zhou, Hao; Cheng, Gui-Qiang; Huang, Xiao-Bo; Hou, Cheng-Lin (European Journal of Taxonomy, 2023)
Two new species, Russula pseudopunicea C.L.Hou, G.Q.Cheng & H.Zhou sp. nov. and R. wulingshanensis C.L.Hou, G.Q.Cheng & H.Zhou sp. nov., from Yanshan mountains in North China are described herein based on morphological and phylogenetic analyses of nrITS, and nrLSU-rpb2-mtSSU gene regions. Morphologically, R. pseudopunicea sp. nov. is characterised by a reddish brown, light brown to brownish orange pileus with a greyish yellow margin, subglobose to broadly ellipsoid basidiospores with warts forming a partial reticulum and pleurocystidia turning grey to purplish red in sulfovanillin. Russula wulingshanensis sp. nov. is characterised by a purple pinkish pileus with a grey-white to grey-purple margin, subglobose to broadly ellipsoid basidiospores with isolated warts, and pileocystidia turning black in sulfovanillin. Phylogenetic and morphological analyses resolved the two species in Russula subg. Heterophyllidia. Russula pseudopunicea sp. nov. and R. wulingshanensis sp. nov. were placed in the lineages of subsect. Virescentinae and subsect. Griseinae, respectively.